A Deeper Insight on the Stability of Water-Induced Reconstruction of Anatase (001) Surface - Giuseppe Zollo; Eugenio Vitale (Applied Sciences, 2018)
TiO <semantics> 2 </semantics> anatase (001) surface has been indicated for many years as a potential system for water dissociation and hydrogen production. Surface reconstruction periodicity of TiO <semantics> 2 </semantics> anatase (001) in water is revised on the basis of the new water induced reconstruction model that accounts for dissociative water adsorption in the first monolayer and self-assembling of surface hydroxyls. The study has been performed in the context of first principles total energy calculations on the basis of state of the art Density Functional Theory. Different surface periodical structures have been studied and compared in terms of residual surface stress and surface reactivity. While a preference seems to emerge for the (2 × 3) surface reconstruction, there are indications that this configuration might not occur spontaneously in bulk water.